Differential actions of spinal analgesics on mono-versus polysynaptic Aδ-fibre-evoked field potentials in superficial spinal dorsal horn in vitro - Ruscheweyh, Ruth; Sandkühler, Jürgen (Pain, 2000)
Processing of nociceptive information can be modulated at various levels in spinal cord that may range from changes of neurotransmitter release from primary afferent Aδ- or C-fibres to excitability changes of spinal interneurones or motoneurones. The site and mechanism of action of spinal analgesics has been assessed with a number of in vivo and in vitro methods with sometimes conflicting results. Here, we have used transverse spinal cord slices with attached dorsal roots to simultaneously record mono- and polysynaptic Aδ-fibre-evoked field potentials in superficial spinal dorsal horn. Two classical spinal analgesics, morphine and clonidine, and the metabotropic glutamate receptor agonist (1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid ((1S,3R)-ACPD) differentially affected mono- and polysynaptic Aδ-fibre-evoked transmission in spinal dorsal horn. Polysynaptic responses were dose-dependently inhibited while the monosynaptic response remained unaffected. These results suggest that spinal analgesics may preferentially affect polysynaptic but not monosynaptic Aδ-fibre-evoked responses in superficial spinal dorsal horn.
Gesehen am 04.05.2021